Effects of Outsourcing Food and Beverage Functions on Customers' Perceptions of Hotels' Service Quality in Dubai - Valeva, Yana Ilieva (2010)
The focus of this study is the customers’ perceptions of service quality in Dubai Hotel Industry. Dubai is one of the newest and most successful tourist destinations that build and develop itself in days of intense competition and globalization. Every well established International brand in Hospitality in today’s world is presented in this tourist destination. This fact has created great opportunities for hotels to link up with aspiring restaurateurs who can give individuality to their restaurants. Outsourcing has become an important strategic tool of hotel management, but as any tool of business it has its own advantages and disadvantages. In Dubai Hospitality industry it is very common to see food and beverage outlets that have been outsourced. The author believes that outsourcing of food and beverage function by hotels should have affected the service quality within the industry. To gain insights on this topic, the author explores the Gap Model of service quality (Parasuraman, Zeithaml, Berry, 1985) and attempts research by conducting amended SERVQUAL to twelve in-sourced and outsourced restaurants from ten randomly selected hotels in Dubai. The analysis of the collected data provided significant results. The most important to the customers in Dubai hotel restaurants is to keep their promises, particularly promises about the service outcomes and core service attributes, which is food and beverages quality. Food and beverage services are viewed by Dubai customers as an integral part of the hospitality product. Hotel restaurants support and steer the hotel’s image and are elements of the guests’ overall expected hotel experience. The hotels’ guests perceive outsourced restaurants as better service quality provider, which affects positively Hotels brand reputation, but Customer Gap is still identified. One of the most important quality dimensions to Dubai hotels guests is “Reliability”, which is the ability to perform the promised service dependably and accurately. The customers’ perception toward “Empathy” quality dimension is not affected by outsourcing food and beverage function. Regardless the function is self-managed or outsourced, Dubai Hotels are facing major issue of low skilled staff with little or no qualification in F&B field that affects negatively the guests’ overall quality perception. At the end, the author summarizes the valuable conclusions of this study and suggests implications for management and further improvements of service quality in hotels.